Assessing Quality in Advance Care Planning Documentation: A Survey of Current Methods. (August 2022) - Berkowitz, Callie M.; Ma, Jessica; Lowe, Jared; Dolor, Rowena J.
Background: High-quality advance care planning (ACP) documentation facilitates the communication of patients' wishes as they progress in their disease course and travel between health care settings. No consensus exists regarding evaluation of documentation quality, and diverse strategies for assessing quality have been adopted in clinical ACP studies. Methodology: We conducted a literature review in PubMed and via manual search to identify clinical studies that assessed ACP quality or completeness as an outcome measure over a 5-year period. Studies that treated ACP as a binary outcome variable (present or absent), studies that took place outside of the US, and studies in pediatric populations were excluded from review. Results: We identified 11 studies for inclusion in our review. Across study methodologies, the following 8 quality domains were identified: discussion frequency, documentation accessibility, discussion timing, health care proxy, health goals or values, scope of treatment/code status, prognosis/illness understanding, and end of life (EOL) care planning. Each study assessed between 2 and 6 domains. Divergent methods for assessing quality domains were utilized, including manual qualitative analysis and natural language processing techniques. Conclusion: Defining and measuring the quality of documentation is critical to developing ACP programs that improve patient care. Our review provides an adaptable framework centered around quality domains.